2022
DOI: 10.1177/1357633x221136305
|View full text |Cite
|
Sign up to set email alerts
|

Telehealth in cancer care during the COVID-19 pandemic

Abstract: Introduction The Victorian COVID-19 Cancer Network (VCCN) Telehealth Expert Working Group aimed to evaluate the telehealth (TH) experience for cancer patients, carers and clinicians with the rapid uptake of TH in early 2020 during the COVID-19 pandemic. Methods We conducted a prospective multi-centre cross-sectional survey involving eight Victorian regional and metropolitan cancer services and three consumer advocacy groups. Patients or their carers and clinicians who had TH consultations between 1 July 2020 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 22 publications
3
7
0
Order By: Relevance
“…Clinicians and patients were congruent in expressing convenience, safety and improved access to care as benefits of telehealth, consistent with previously reported research 18,20,23,41 . Patients also reported that telehealth allowed family and friends to be present in a supportive role during the consultation, without a major impact on the family member/friend's routines.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…Clinicians and patients were congruent in expressing convenience, safety and improved access to care as benefits of telehealth, consistent with previously reported research 18,20,23,41 . Patients also reported that telehealth allowed family and friends to be present in a supportive role during the consultation, without a major impact on the family member/friend's routines.…”
Section: Discussionsupporting
confidence: 81%
“…Rapid transition to telehealth resulting from COVID‐19 44 may not have allowed sufficient time to source adequate technology and provide appropriate training for both clinicians and patients, which may also explain why the majority of telehealth consultations in this study were conducted via telephone rather than audio‐visually. Additionally, both patients and clinicians perceived telehealth communication to be less personal and more difficult due to reduced availability of non‐verbal cues, consistent with the findings from other cancer groups 12,14,23,39,41 . Good interpersonal communication and rapport are especially important when symptoms and emotional issues are discussed, 21,40 and have been shown to be improved by the inclusion of an audio‐visual medium 19,41 …”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…Across cancer care, telehealth has been employed in services such as outpatients, pre‐therapy surgical reviews, monitoring, chemotherapy, and clinical trials 6–9 . Telehealth has successfully ensured the continuation of cancer care, particularly for those people living in rural or regional areas, where specialist services are limited 10,11 …”
Section: Introductionmentioning
confidence: 99%
“…[6][7][8][9] Telehealth has successfully ensured the continuation of cancer care, particularly for those people living in rural or regional areas, where specialist services are limited. 10,11 The long-term sustainability of telehealth depends on a number of key requirements, including empowering consumers to confidently seek and engage in telehealth. 12 As end-users, consumers have a unique perspective regarding their treatment and whether it complies with their expectations of care.…”
Section: Introductionmentioning
confidence: 99%